1996
DOI: 10.1046/j.1471-4159.1996.67041540.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Vulnerability of Nucleus Accumbens Dopamine Binding Sites to Low‐Level Lead Exposure: Time Course of Effects and Interactions with Chronic Dopamine Agonist Treatments

Abstract: This study examined the hypotheses that low‐level lead (Pb) exposure would increase dopamine (DA) binding sites, would do so preferentially in nucleus accumbens, and that such effects would be modified by concurrent DA agonist treatment. D1‐like and D2‐like binding sites and the dopamine transporter (DT) were measured autoradiographically in caudate‐putamen and nucleus accumbens of rats exposed from weaning to 0, 50, or 150 ppm Pb acetate drinking solutions with or without concurrent chronic intermittent intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 31 publications
(44 reference statements)
1
29
0
Order By: Relevance
“…Because these changes are associated with the reinforcement properties of methamphetamine, and inasmuch as lead exposure is known to antagonize mesolimbic dopamine systems (cf. CorySlechta, 1995;Pokora et al, 1996), it is reasonable to assert that the attenuation of methamphetamine reinforcement in the present studies derived at least partly from the effects of developmental lead exposure on dopamine function. Importantly, it would appear that such effects are long-lasting and potentially permanent (cf.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Because these changes are associated with the reinforcement properties of methamphetamine, and inasmuch as lead exposure is known to antagonize mesolimbic dopamine systems (cf. CorySlechta, 1995;Pokora et al, 1996), it is reasonable to assert that the attenuation of methamphetamine reinforcement in the present studies derived at least partly from the effects of developmental lead exposure on dopamine function. Importantly, it would appear that such effects are long-lasting and potentially permanent (cf.…”
Section: Discussionmentioning
confidence: 70%
“…As noted, developmental lead exposure results in behavioral changes across different psychoactive drugs. Because methamphetamine operates in part to interfere with the dopamine transporter and therein enhance dopamine transmission (Ranaldi and Poeggel, 2002), and because lead has a lasting impact at this site (Pokora et al, 1996), it would seem reasonable to examine lead/methamphetamine interactions. Accordingly, the purpose of the present project was to inform on the effects of perinatal lead exposure on methamphetamine dose-effect performance (Experiment 1), and to determine potential differences in progressive ratio responding which is believed to provide an index of motivation to seek the drug (Experiment 2).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…A pronounced decrease in D 2 -like binding sites was also observed in the nucleus accumbens at the 150 ppm level of exposure for all time points measured. Pokora et al (1996) concluded in this study that the nucleus accumbens was preferentially affected by lead relative to the striatum.…”
mentioning
confidence: 65%
“…In particular, it involved a much more extensive developmental exposure that included both the prenatal and postnatal periods. Pokora et al (1996) used a postweaning exposure protocol similar to the one used in the present study to examine the time course of the effects of lead on DA D 1 -like and D 2 -like receptor binding in the striatum and nucleus accumbens. In the striatum, lead exposure at the 150 ppm level caused only a small and transient decrease in D 1 -like binding after 8 months of lead treatment (no longer significant after 12 months), but no effect at the earlier 2-week time point.…”
mentioning
confidence: 99%
“…Thus, both Pb and stress target low SES populations. Secondly, both Pb and stress act on brain mesocorticolimbic and hippocampal dopamine and glutamate systems (Diorio et al 1993;Lowy et al 1993;Piazza et al 1996;Pokora et al 1996;Cory-Slechta et al 1998;Rouge-Pont et al 1998;Cory-Slechta et al 1999;Barrot et al 2000;Moghaddam 2002), which may in fact explain their common consequences, including cognitive dysfunction and attention deficits (Dohrenwend, 1973;Bellinger et al, 1994;Schwartz, 1994;Anderson and Armstead, 1995a;Cory-Slechta, 1995;Needleman et al, 1996;Dietrich et al, 2001;Bradley and Corwyn, 2002). Third, the mesocorticolimbic dopamine system, a key target of Pb effects on behavior (Cory-Slechta 1995;Cory-Slechta et al 1996;Cory-Slechta et al 1997a;Cory-Slechta et al 1997b;CorySlechta et al 1998;Cory-Slechta et al 2002;Abbott et al 2003) has extensive interactions with the hypothalamic-pituitary-adrenal (HPA) axis, the system that coordinates the body's physiological response to stress (Vazquez 1998).…”
Section: Introductionmentioning
confidence: 99%